The Effect of Cognitive Restructuring Techniques to Reduce Academic Procrastination of High School Students - Epin Candra Buana; Ebtaniz Zulwidyaningtyas (International Journal of Counseling and Psychotherapy, 2024)
Academic procrastination is a major problem faced by many students in school, this can lead to decreased student productivity in doing assignments. The purpose of this technique is to help students change negative thought patterns that cause academic procrastination behavior into more productive positive thoughts. The research method used in this study is the Mix Method with Sequential Explanatory design. This research was conducted in 2023, located at SMP Negeri 1 Kepung. Data collection using a questionnaire. Data analysis used the t-test. The results showed that cognitive restructuring techniques through group counseling had an effect in reducing students' academic procrastination. The contribution of this research Results are used as a source of knowledge, especially in the field of counseling guidance regarding group counseling on students' academic procrastination behavior.